The hererogeneity of Science Teachers Speak: Analyzing ways to think the heat concept (Research, Society and Development, 2021)
This article aimed to analyze the ways of thinking about the concept of heat that emerge in the speech of teachers from two public schools in São Raimundo Nonato-PI. For this, we are guided by the theory of conceptual profiles that discusses the polysemy of scientific concepts worked on in the classroom, precisely the concept of heat, as this has great relevance within the teaching of Science. This research has a descriptive qualitative character, carried out from the collection, analysis and mapping of the statements of two Science teachers from the 9th year of Elementary School. The operationalization of this research was divided into two stages, the first was the application of a questionnaire containing nine questions, the second was through observation of three Science classes, whose objective was to verify the different ways of speaking the concept of heat when it is taught in the classroom. Based on our results, we verified different ways of thinking about the concept of heat in the teachers' speech, namely: Rationalist, substantialist, realist, empirical and animist. It is noteworthy that we could observe that the professors teach and articulate the heterogeneity of the concept of heat in their classes, however in a shallow way, that is, they are not aware of the meanings that this concept presents. We emphasize, from the discussions presented here, that we intend to continue our research involving the use of conceptual profiles in the understanding, planning and contextualization of science teaching.